Structural and site-specific characterization of distinctive N-glycans with heavy fucosylation in human semen - Miaomiao Xin; Yintai Xu; Shanshan You; Cheng Li; Jiechen Shen; Bojing Zhu; Qiaohong Zhao; Juanzi Shi; Shisheng Sun (Carbohydrate Polymer Technologies and Applications)
Heavy fucosylation (fucose residues ≥ 6 per glycan) has been previously reported in human semen with unclear precise site-specific glycan structures. In current study, we characterized heavily fucosylated glycoproteins as a distinctive feature of human spermatozoa (HS) and seminal plasma (HSP), with a precise definition of glycan structural features at the glycosite-specific level. There were 49 unique heavily fucosylated intact glycopeptides (IGPs) at 15 N-glycosites from 12 glycoproteins identified in HS, and 188 unique heavily fucosylated IGPs at 58 N-glycosites from 37 glycoproteins in HSP. Among these heavily fucosylated glycoproteins, 10 were shared in HS and HSP, 2 were detected only in HS and 17 only in HSP. Almost all heavily fucosylated glycans were complex N-glycans with core fucosylation and Lewis antennary, among which CLU were glycosylated by ten and nine fucoses per glycan in HS and HSP, respectively. Moreover, these heavily fucosylated glycans varied from tri- to hexa-antennas. Notably, the N-glycan structures on shared heavily fucosylated glycoproteins were more complex in HSP than in HS. These heavily fucosylated glycoproteins identified in human semen represent a valuable and distinctive resource for glycopeptide studies, offering significant potential for advancing glycoproteomic methodologies and clinical research into male infertility.